Interactive Storytelling with Quantum Computing Exploring the New Design Practices in Interactive Storytelling Using the Emerging Quantum Technologies - Skult, Natasha (fi=Turun yliopisto|en=University of Turku|, 2026)
Quantum computing QC is emerging as a transformative technology, yet its implica tions for game design and interactive storytelling remain largely unexplored within the games industry. This thesis investigates the opportunities and challenges of inte grating QC into interactive media, in particular games, with the focus on its impact on game design methodologies, narrative structures, and user experience. Through a game design perspective, this thesis examines: (1) the concrete pros and cons of using quantum over classical computing in interactive media, (2) how QC challenges the role of game designers and established best practices, and (3) how user experience differs when engaging with quantum-enhanced storytelling. The study explores current applications of quantum mechanics in game development, AI driven narrative techniques, and new design methodologies tailored for QC-based ex periences. Case studies include C.L.A.Y – The Last Redemption, QWiz, and QPlay ground, which offer insights into both designer and player perspectives, highlighting challenges such as predicting user interaction on future QC platforms and adapting design workfows to the principles of quantum computing. By synthesizing fndings from interactive media, QC simulations, and player experiences, this thesis proposes a clear set of guidelines for game designers and quantum physicists as industry professionals, as well as academic researchers, to uti lize in designing interactive storytelling experiences with quantum computing. The results provide a foundation for future explorations into how QC can redefne immer sion, procedural generation, and player engagement in next-generation game design practices.